Outcome of neonates born through Meconium stained amniotic fluid in tertiary health care centre - N., Girish; M. R., Shravani; C. D., Tharashree; B., Sunil (International Journal of Contemporary Pediatrics, 2018)
Background: Meconium Aspiraion Syndrome (MAS) is an important cause of morbidity and mortality among newborns in the developing world. Meconium stained amniotic fluid (MSAF) occurs in approximately 13% of all live births. Methods: This was a prospective observational study to assess the risk factors related with MSAF deliveries and MAS. All the details regarding mode of delivery, APGAR score (AS), birth weight, fetal distress, maternal age, any maternal illness, gestational age, clinical course, outcome was recorded and evaluated. Results: In the present study total of 100 babies born through MSAF were included of which the incidence of respiratory distress was noted in 62% (62 babies). Conclusions: Appropriate monitoring of respiratory distress at birth and assessing the high-risk cases will surely help in reducing the morbidity and mortality in vigorous babies born through MSAF.